Π–π Stacking Interaction in an Oxidized CuII–Salen Complex with a Side‐Chain Indole Ring: An Approach to the Function of the Tryptophan in the Active Site of Galactose Oxidase1. Issue 32 (13th May 2019) - Oshita, Hiromi; Suzuki, Takashi; Kawashima, Kyohei; Abe, Hitoshi; Tani, Fumito; Mori, Seiji; Yajima, Tatsuo; Shimazaki, Yuichi
Abstract: In order to gain new insights into the effect of the π–π stacking interaction of the indole ring with the Cu II –phenoxyl radical as seen in the active form of galactose oxidase, we have prepared a Cu II complex of a methoxy‐substituted salen‐type ligand, containing a pendent indole ring on the dinitrogen chelate backbone, and characterized its one‐electron‐oxidized forms. The X‐ray crystal structures of the oxidized Cu II complex exhibited the π–π stacking interaction of the indole ring mainly with one of the two phenolate moieties. The phenolate moiety in close contact with the indole moiety showed the characteristic phenoxyl radical structural features, indicating that the indole ring favors the π–π stacking interaction with the phenoxyl radical. The UV/Vis/NIR spectra of the oxidized Cu II complex with the pendent indole ring was significantly different from those of the complex without the side‐chain indole ring, and the absorption and CD spectra exhibited a solvent dependence, which is in line with the phenoxyl radical–indole stacking interaction in solution. The other physicochemical results and theoretical calculations strongly support that the indole ring, as an electron donor, stabilizes the phenoxyl radical by the π–π stacking interaction. Abstract : Let's stack : A Cu II –phenoxyl radical complex having a pendent indole moiety was synthesized and characterized as an active site model of galactose oxidase (see figure). The proximal indole ring shows a selective π–π stacking interaction with the phenoxyl radical moiety and serves as its electron donor. As a result, the phenoxyl radical is more stabilized than that in a complex without the indole ring.